Preparation method and application of a bifunctional shaped skeleton cobalt catalyst

By using the preparation method of a dual-function molded skeleton cobalt catalyst in the IPDA hydrogenation reaction, the problems of easy powderization and low strength of the existing catalysts are solved, and efficient and stable IPDA preparation is achieved, reducing costs.

CN116474794BActive Publication Date: 2025-04-04WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210035051.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2025-04-04
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

The existing skeleton cobalt catalysts are easily powdered in the hydrogenation reaction of IPDA, and have low strength, resulting in increased costs and poor reaction stability.

Method used

The preparation method of a dual-function molded skeleton cobalt catalyst is adopted. By adding a Rainy precursor during the preparation of the gel and activating it in situ, combining metal additives and binders to form a high-strength catalyst.

Benefits of technology

The strength and lifetime of the catalyst are significantly improved, the hydrolysis reaction of intermediate products is inhibited, the yield of IPDA is improved, and the activity and stability of the catalyst are maintained.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the preparation of a zirconium-based skeleton cobalt catalyst with dual-functional catalytic effects. The preparation method is as follows: preparing a zirconium oxide synthetic sol; smelting cobalt and aluminum alloy, and crushing them into alloy powder; adding the cobalt aluminum alloy powder into the gel, drying, tableting, and activating to obtain a zirconium-based skeleton cobalt catalyst. The catalyst is characterized in that it has a certain acidity compared with the common Raney catalyst. When applied to the amination and hydrogenation of isophoronenitrile (IPN) to prepare isophoronediamine (IPDA), it can simultaneously play the role of imidization, hydrogenation, and inhibiting the hydrolysis of the intermediate product isophoronenitrile imine, thereby improving the conversion rate of IPN. Experimental measurements show that the IPN conversion rate can reach 100%, the IPDA selectivity is greater than 99%, and the by-products are greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent relates to the preparation and application of a bifunctional skeleton Co catalyst, which can be used for the amination and hydrogenation of 3-cyano-3,5,5-trimethylcyclohexanone (IPN) to prepare 3-aminomethyl-3,5,5-trimethylcyclohexylamine (IPDA). Background Art

[0002] 3-aminomethyl-3,5,5-trimethylcyclohexylamine (isophorone diamine, IPDA) is mainly used to prepare isophorone diisocyanate, polyamide and other polymer materials, and is also used in curing agents, etc. These materials have good chemical resistance, thermosetting and other advantages. IPDA is a mixture of cis / trans isomers, and IPDA with different cis / trans isomer ratios is suitable for different fields. According to German patent DEA421154, IPDA with less than 60% cis isomer is conducive to reducing the maximum curing temperature of epoxy resin, while IPDA with more than 70% cis isomer content is conducive to increasing the reaction rate of polymer resin.

[0003] US patents US3352913 and US570569 disclose a two-step process for producing IPDA, which is also the mainstream process for industrial production at present, that is, 3-cyano-3,5,5-trimethylcyclohexanone (isophorone nitrile, IPN) reacts with excess ammonia, imidizes under the action of an acidic or alkaline catalyst to obtain isophorone nitrile imine, and then reacts with hydrogen to obtain isophorone diamine under the action of a Raney catalyst. The reaction of isophorone nitrile with ammonia to generate isophorone nitrile imine is a reversible reaction, and its reverse reaction is the hydrolysis reaction of Schiff base. The generated IPN will be directly hydrogenated to obtain amino alcohol, which is also the most important by-product of the reaction.

[0004] In addition, the catalyst suitable for the hydrogenation reaction in the second step of the above process is a skeleton cobalt catalyst. The US patent US6087296 discloses a method for preparing a skeleton cobalt catalyst, specifically, directly activating Co-Al alloy powder by alkali treatment. However, the yield of this method is low, and the catalyst strength is low and easy to pulverize, which indirectly increases the cost. Patents CN1557918A and US6489521 disclose methods for preparing molded skeleton cobalt catalysts. These patents use inorganic or organic binders and metal powders mixed together to prepare skeleton cobalt catalysts through a series of methods, but there is no example of application to IPDA reaction. Summary of the invention

[0005] In view of the above-mentioned defects, the present invention provides a type of skeleton cobalt catalyst with imidization-hydrogenation dual functions. At the same time, the catalyst is stronger than the traditional skeleton cobalt catalyst and has a longer life.

[0006] Another object of the present invention is to use the catalyst, which is used as a catalyst for preparing IPDA from IPN. On the one hand, it can inhibit the hydrolysis reaction of the intermediate product isophoronenitrile imine, and at the same time has hydrogenation performance, thereby greatly improving the yield of IPDA.

[0007] In order to achieve the above objectives, the present invention provides a method for preparing a bifunctional formed skeleton cobalt catalyst, the scheme is as follows:

[0008] (1) preparing a Co-Al alloy, crushing it into alloy powder, and adding a certain amount of metal additives and binders;

[0009] (2) preparing zirconium oxide synthetic gel;

[0010] (3) The products obtained in step (1) and step (2) are mixed, dried, pressed into tablets, and activated with alkaline solution in situ to obtain a catalyst.

[0011] The advantage of this solution is that the Raney precursor is added during the preparation of the gel, and then activated in situ. The Raney and acid catalysts are coupled during the preparation process, rather than the traditional loading, which strengthens the interaction between the catalysts and ensures the catalytic performance. At the same time, in-situ activation is used, which fundamentally solves the strength problem of the coupled catalyst, prevents powdering and agglomeration, and maintains its catalytic activity to the maximum extent.

[0012] In the method of the present invention, in step (1), the mass ratio of cobalt to aluminum in the cobalt-aluminum alloy is 0.5-1.5, the smelting temperature is 1600-1800° C., stirring is applied during smelting, the stirring time is 2-5 minutes, and the stirring rate is 20-50 r / min. After stirring, it is naturally cooled to room temperature to obtain an alloy block. The diameter of the particles obtained after the alloy block is crushed is between 100-400 mesh, preferably 200-300 mesh.

[0013] In the method of the present invention, in step (1), the binder used is one or more of graphite, field blue powder, and cellulose. The addition amount is 5-20wt%, based on the mass of the alloy powder. The conventional IPDA hydrogenation catalyst is to directly activate the alloy block and apply it to the fixed bed. If the hydrogenation performance of the catalyst is to be improved, the degree of activation must be increased. If the degree of activation is deepened, the strength of the catalyst is directly reduced. The strength is reduced, and the catalyst is easy to pulverize during the reaction, polluting the material.

[0014] In the method of the present invention, in step (1), the added metal additive is one or more of Ca, Mg, P, Ni, Pt, Cr, Co, Ti, Mg, B, Zn, and Mo, and the added amount is 0.1-5wt% based on the mass of the alloy powder.

[0015] In the method of the present invention, step (2) is used to prepare zirconium oxide synthetic gel. A certain amount of tetrabutyl zirconate, deionized water, and ruthenium acetate are uniformly mixed in a mass ratio of 1:x:y, wherein x is 1-20, preferably 2-10, and y is 1-10, preferably 2-8. Then sulfuric acid is added to adjust the pH to 1-5. Stir for 5-72 hours to obtain zirconium oxide synthetic gel.

[0016] In the method of the present invention, in step (3), the alloy powder and the zirconium oxide gel are mixed in a mass ratio of 1:5-15, preferably 1:6-12, and then dried at 80-100°C for 6-12 hours. Then, the tablets are pressed. The tablet pressing mold is a cylinder with a diameter of 1-5mm and a height of 2-6mm. Preferably, the cylinder has a diameter of 2-4mm and a height of 3-5mm.

[0017] In the method of the present invention, in step (3), the activation method used is in-situ alkali solution washing activation. The alkali used is one of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water. The required alkali solution concentration is 5-30wt%, preferably 10-25wt%. The activation temperature is 60-90°C, preferably 70-90°C. The activation time is 1-3h, and the alkali solution air velocity is controlled at 5-20h during activation. -1 .

[0018] The high-strength bifunctional catalyst with both acidic and hydrogenation properties obtained by this method is applied to the fixed bed IPN one-step method for preparing IPDA. A single tube reactor is used for evaluation, and the catalyst is loaded with 50 mL. Ammonia, hydrogen, and IPN are mixed and then enter the reactor, wherein the ammonia ratio to IPN is 1.2-2.5:1 (molar ratio), and the hydrogen ratio to IPN is 3-10:1 (molar ratio). The reaction pressure is 0.3-0.8Mpa, and the temperature is 100-300°C. The overall space velocity is controlled at 50-200h -1 .

[0019] At present, the preparation of IPDA from IPN is a two-step reaction. The first step is the reaction of IPN with ammonia via an acidic catalyst (silicon and titanium oxides) to generate IPDI, and then IPDI reacts with hydrogen and liquid ammonia via a Raney catalyst to generate IPDA. Since the first step is a reversible reaction, the high conversion rate of IPN cannot be guaranteed. The IPN regenerated by the reverse reaction will be directly hydrogenated to generate amino alcohol in the second step, which is not good for the quality of the product. This patent couples the Raney catalyst to the acidic catalyst through a certain scheme, and the bifunctional catalyst with imidization and amination hydrogenation is prepared at the same time, which directly upgrades the previous two-step reaction to a one-step reaction, greatly improving the conversion rate and selectivity.

[0020] The pressures described in the present invention are all gauge pressures.

[0021] The positive effects of the present invention are:

[0022] (1) The skeleton Co catalyst used in the traditional IPN hydrogenation to prepare IPDA is prone to powderization and contamination during the reaction process, and its strength is relatively low. However, this catalyst obtains a high-strength molded skeleton cobalt catalyst through reasonable molding methods, which improves the mechanical strength of the catalyst while not affecting the catalyst hydrogenation effect. This indirectly improves the stability and safety of the reaction evaluation process.

[0023] (2) Zirconium oxide is introduced into the catalyst during the molding process. Its presence will provide certain acidic sites, which is conducive to promoting the forward progress of the isophoronenitrile imidization reaction. As a Schiff base, isophoronenitrile imine is unstable and easily hydrolyzed to form isophoronenitrile, while direct hydrogenation of isophoronenitrile will affect the yield of the reaction. Acidic sites, as an active site to protect isophoronenitrile imine, can significantly reduce the amount of by-products in the product, thereby improving the activity and stability of the catalyst. DETAILED DESCRIPTION

[0024] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0025] The N2 adsorption method (BET) used in the embodiments of the present invention is used to measure the specific surface area and pore structure of the catalyst microspheres. The instrument model is ASP2020, produced by Micromeritics Instruments, Inc., USA.

[0026] The inductively coupled plasma optical emission spectrometer (ICP-OES) used in the examples of the present invention is produced by Agilent Technologies, model 720 ICP-OES.

[0027] The particle strength tester used in the embodiment of the present invention is a digital particle strength tester produced by Jiangyan Analytical Instrument Factory, model KC-3.

[0028] The gas chromatography analysis conditions used in the examples of the present invention are: Agilent DB-5 chromatographic column, injection port temperature: 280°C; detector temperature: 280°C; H2 flow rate: 35ml / min; air flow rate: 360ml / min. The column box temperature program is: initial temperature -100°C, heating rate of 20°C / min, hold for 1min; 100-280°C, heating rate of 15°C / min, hold for 8min.

[0029] Example 1

[0030] Mix 350g of metal cobalt and 650g of metal aluminum and put them into a smelting crucible. Then place the crucible in a smelting furnace, heat it to 1700℃, keep it for 5min, and start stirring at a stirring rate of 40r / min. After completion, pour the slurry on a graphite plate and cool it naturally to room temperature to obtain an alloy block. Use a crusher to crush the alloy block into powder, sieve out a sample of 200-300 mesh with a sieve to obtain an alloy powder. Take 50g of alloy powder, 6.55g of sesbania powder, 0.3g of copper powder, and 0.2g of magnesium powder, mix them evenly and set aside.

[0031] Mix 20g of tetrabutyl zirconate, 40g of deionized water and 160g of ruthenium acetate, add sulfuric acid to adjust the pH to 3. After stirring for 24 hours, add 40g of alloy powder doped with binder and metal. Press into a cylinder with a diameter of 2mm and a height of 3.5mm. Dry at 100℃ for 12h and set aside.

[0032] Place in the reaction tube for in-situ activation, use 25wt% sodium hydroxide solution, circulate for 2h at 70℃, and the space velocity is 8h -1 After completion, the catalyst was washed with deionized water until it became neutral.

[0033] The obtained catalyst was characterized and its BET specific surface area was measured to be 62 m 2 / g, and the compression strength is 340N / grain.

[0034] The catalyst was evaluated in the IPN to IPDA reaction. 50 mL of catalyst was loaded into a single tube reactor at a space velocity of 50 h -1 , the molar ratio of ammonia to IPN was 1.2:1, the molar ratio of hydrogen to IPN was 3.2:1, the reaction pressure was 0.3Mpa, and the temperature was 100°C. It was run continuously for 100 hours, and samples were taken every 10 hours for chromatographic analysis. The results are as follows: the average conversion rate of IPN was 99.3%, the average selectivity of IPDA was 99.9%, and the other products (mainly amino alcohols) were 0.8%. ICP-OES analysis of the product did not find the presence of metals such as Co and Al, indicating that the catalyst was not pulverized and the catalyst morphology remained intact.

[0035] Example 2

[0036] The preparation method of Co-Al alloy powder is shown in Example 1.

[0037] Take 50g alloy powder, 3g graphite, 0.5g boron powder and 0.2g magnesium powder, mix well and set aside.

[0038] Mix 20g of tetrabutyl zirconate, 60g of deionized water and 80g of ruthenium acetate, add sulfuric acid to adjust the pH to 1.5. After stirring for 48 hours, add 25g of alloy powder doped with binder and metal. Press into a cylinder with a diameter of 2.5mm and a height of 3.5mm. Dry at 80℃ for 9h and set aside.

[0039] Place in the reaction tube for in-situ activation, take 20wt% sodium hydroxide solution, circulate at 60℃ for 3h. The air velocity is set to 11h -1 After completion, the catalyst was washed with deionized water until it became neutral.

[0040] The obtained catalyst was characterized and its BET specific surface area was measured to be 65 m 2 / g, and the compression strength is 335N / grain.

[0041] The catalyst was evaluated in the IPN to IPDA reaction. 50 mL of catalyst was loaded into a single tube reactor at a space velocity of 120 h -1 , the molar ratio of ammonia to IPN was 1.85:1, the molar ratio of hydrogen to IPN was 6.5:1, the reaction pressure was 0.52Mpa, and the temperature was 150°C. It was run continuously for 100 hours, and samples were taken every 10 hours for chromatographic analysis. The results are as follows: the average conversion rate of IPN was 100%, the average selectivity of IPDA was 99.3%, and the other products (mainly amino alcohols) were 0.5%. ICP-OES analysis of the product did not find the presence of metals such as Co and Al, indicating that the catalyst was not pulverized and the catalyst morphology remained intact.

[0042] Example 3

[0043] The preparation method of Co-Al alloy powder refers to Example 1, and the mass ratio of cobalt to aluminum alloy is changed to 1.3.

[0044] Take 50g alloy powder, 9g cellulose, 0.8g molybdenum powder and 0.2g phosphorus powder, mix them evenly and set aside.

[0045] Mix 20g of tetrabutyl zirconate, 80g of deionized water and 100g of ruthenium acetate, add sulfuric acid to adjust the pH to 2.5. After stirring for 24 hours, add 25g of alloy powder doped with binder and metal. Press into a cylinder with a diameter of 2mm and a height of 4.5mm. Dry at 90℃ for 6h and set aside.

[0046] Put the metal sheet into the reaction tube, take 25wt% sodium hydroxide solution, circulate at 80℃ for 1.5h. Set the air velocity to 18h -1 After completion, the catalyst was washed with deionized water until it became neutral.

[0047] The obtained catalyst was characterized and its BET specific surface area was measured to be 65 m 2 / g, and the compression strength is 320N / grain.

[0048] The catalyst was evaluated in the IPN to IPDA reaction. 50 mL of catalyst was loaded into a single tube reactor at a space velocity of 200 h -1 , the molar ratio of ammonia to IPN was 2.4:1, the molar ratio of hydrogen to IPN was 9.5:1, the reaction pressure was 0.75Mpa, and the temperature was 260℃. It was run continuously for 100 hours, and samples were taken every 10 hours for chromatographic analysis. The results are as follows: the average conversion of IPN was 100%, the average selectivity of IPDA was 99.9%, and no amino alcohol was detected. The product was analyzed by ICP-OES, and no metals such as Co and Al were found, indicating that the catalyst was not pulverized and the catalyst morphology remained intact.

[0049] Comparative Example 1

[0050] A commercial IPN hydrogenation catalyst for preparing IPDA (purchased from Grace Chemical Company, USA) was characterized and evaluated according to the evaluation method in Example 1. The industrial catalyst preparation method of this company is to directly activate the alloy block without the step of extrusion. The specific surface area was measured to be 61m 2 / g, the pressure strength is 290N / particle, the average IPN conversion rate is 99.5%, the average IPDA selectivity is 99.1%, and a small amount of Co is detected in the reaction liquid, indicating that the catalyst is pulverized. The catalytic performance of this catalyst is slightly worse than that of the catalyst in this patent.

[0051] Comparative Example 2

[0052] Referring to the preparation method of Raney catalyst in Example 2 of patent CN1557918A, the Ni-Al alloy was replaced with Co-Al alloy. The catalyst was characterized and the specific surface area of ​​the catalyst was 25m 2 / g, and the pressure strength is 200N / particle. The reaction evaluation is carried out in the same manner as in Example 1, and the average conversion rate of IPN is 96.3%, and the average selectivity of IPDA is 98.2%. The catalytic performance of the catalyst is inferior to that of the present invention.

Claims

1. A method for preparing a bifunctional shaped skeleton cobalt catalyst, characterized in that: The method comprises: (1) preparing a Co-Al alloy, crushing it into alloy powder, and adding a certain amount of metal additives and binders; (2) preparing zirconium oxide synthetic gel; (3) mixing the products obtained in step (1) and step (2), drying, tableting, and in-situ alkali solution activation to obtain a catalyst; Wherein, in step (1), the metal additive used is one or more of Ca, Mg, P, Ni, Pt, Cr, Co, Ti, Mg, B, Zn, and Mo; In step (2), a certain amount of tetrabutyl zirconate, water and ruthenium acetate are mixed evenly, and then sulfuric acid is added to adjust the pH, and stirred to obtain a zirconium oxide synthetic gel.

2. The method according to claim 1, characterized in that: The mass ratio of cobalt to aluminum in the Co-Al alloy powder prepared in step (1) is 0.5-1.5, and the particle size of the alloy powder obtained by crushing is between 100-400 meshes.

3. The method according to claim 1 or 2, characterized in that: The binder selected in step (1) is one or more of graphite, field blue powder, and cellulose, and the addition amount is 5-20wt% based on the mass of the alloy powder.

4. The method according to claim 1, characterized in that: The amount of the metal additive used in step (1) is 0.1-5 wt % based on the mass of the alloy powder.

5. The method according to claim 1, characterized in that: In step (2), the mass ratio of tetrabutyl zirconate, water and ruthenium acetate is 1:x:y, wherein x is 1-20 and y is 1-10, and then sulfuric acid is added to adjust the pH to 1-5, and stirred for 5-72 hours to obtain zirconium oxide synthetic gel.

6. The method according to claim 1, characterized in that: Mix the alloy powder and zirconium oxide gel in a mass ratio of 1:5-15 and stir evenly.

7. The method according to claim 1, characterized in that: In step (3), the drying temperature is 80-100° C. and the drying time is 6-12 h.

8. The method according to claim 1, characterized in that: The tablet pressing tool is a cylinder with a diameter of 1-5 mm and a height of 2-6 mm.

9. The method according to claim 1, characterized in that: The concentration of alkali solution required for in-situ activation is 5-30wt%; the temperature required for the activation process is 60-90℃, and the activation time is 1-3h; the alkali solution air velocity during activation is controlled at 5-20h -1 .

10. The catalyst prepared by the method according to any one of claims 1 to 9 is used in the amination and hydrogenation of 3-cyano-3,5,5-trimethylcyclohexanone to prepare 3-aminomethyl-3,5,5-trimethylcyclohexylamine.

Citation Information

Patent Citations

  • 3-aminomethyl-3, 5, 5-trialky-1-cyclohexylamine and cyclohexanol compounds

    US3352913A

  • Stock-feeder

    US570569A

  • Raney iron catalyst and a process for hydrogenating organic compounds using said catalyst

    US6087296A

  • Fixed bed catalysts

    US6489521B2

  • Method for preparing ethanol through hydrogenating acetic acid

    CN104557455A